Lumbar septic arthritis and psoas abscess due to Aggregatibacter aphrophilus. (20th April 2011) - Bernard, Fanny; Rossi, Pascal; Lagier, Jean Christophe; Craighero, Fabien; Frances, Yves; Granel, Brigitte
Abstract : Invasive infections due to Aggregatibacter aphrophilus mainly include negative blood culture endocarditis and osteoarticular infections. The authors present herein a rare case of posterior septic arthritis related to A aphrophilus involving lumbar spine with contiguous abscesses of psoas and paravertebral muscles. The infection likely originated from oral cavity. A good outcome was observed after a prolonged and targeted antibiotherapy.